2011
DOI: 10.1111/j.1365-2656.2011.01904.x
|View full text |Cite
|
Sign up to set email alerts
|

Population regulation by habitat heterogeneity or individual adjustment?

Abstract: Summary1. The habitat heterogeneity (HHH) and individual adjustment (IAH) hypotheses are commonly proposed to explain a decrease in reproduction rate with increasing population density. Higher numbers of low-quality territories with low reproductive success as density increases lead to a decrease in reproduction under the HHH, while more competition at high density decreases reproduction across all territories under the IAH. 2. We analyse the influence of density and habitat heterogeneity on reproductive succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 65 publications
(93 reference statements)
1
46
0
Order By: Relevance
“…cold and rainy days) in spring 2009 that negatively affected the productivity of Bonelli’s eagle, which was remarkably low (0.85, n = 40), while the productivity of successful pairs on that breeding season (1.71, n = 17) was similar or even higher than in other years. Apparently, pairs holding good territories are able to rear chicks even in bad years [70], but this does not necessarily implies that the environmental and food supply conditions that these pairs experience are the same over years, as suggested by our results. In particular, the population-year with the highest mean productivity (i.e.…”
Section: Discussionmentioning
confidence: 55%
“…cold and rainy days) in spring 2009 that negatively affected the productivity of Bonelli’s eagle, which was remarkably low (0.85, n = 40), while the productivity of successful pairs on that breeding season (1.71, n = 17) was similar or even higher than in other years. Apparently, pairs holding good territories are able to rear chicks even in bad years [70], but this does not necessarily implies that the environmental and food supply conditions that these pairs experience are the same over years, as suggested by our results. In particular, the population-year with the highest mean productivity (i.e.…”
Section: Discussionmentioning
confidence: 55%
“…Krüger et al. (2012) showed that poor-quality territories of the goshawk were generally only occupied in years with high population density, while only core territories were occupied in years with low population density. Our findings provide limited evidence of accumulation of microorganisms across years being measurable at the level of adults or nestlings.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, individuals may benefit by recognizing spatial variation in habitat quality and settling accordingly and it is widely assumed that both clutch size and reproductive output in territorial birds depend on the quality of their territories [4], [10], [11]. In fact, habitat heterogeneity and despotic settlement have been postulated as the main mechanism of population regulation for territorial birds [10], [12], [13], [14]. Under an ideal free distribution equal competitors select habitats to maximize their individual fitness, whereas under an ideal despotic distribution or more complex distribution models, individuals are unequal competitors and the resources or territories of highest quality are monopolized by the strongest competitors [4].…”
Section: Introductionmentioning
confidence: 99%